LITERASI PENDIDIKAN AGAMA DI ERA REVOLUSI INDUSTI 4.0 MENYONGSONG PENDIDIKAN AGAMA MASYARAKAT 5.0 - I Nyoman Raka (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
This study reveals Hindu religious learning in the 4.0 era, in order to welcome the 5.0 society. Learning problems are limited to only problems: the curriculum, the method of deliver- ing the material, up to the state and quality of the teacher. Theories of religious learning so far, often leave obstacles. The saturation of students in religious learning is often an obstacle. Edu- cational technology in the Industrial Revolution 4.0 era has provided a solution, 'lifelong learn- ing', which can be done anywhere, anytime, in any way, and by anyone. The solution 'learning can be anywhere', has shifted the role of teachers in the education process. The dominance of technology over teachers in the religious learning process occurs. Society 5.0 hopes to use technology as a means to build comfort in human life, including in the context of religious learning. How is Hindu religion learning in the 4.0 industrial revolution era?, what is the role of technology in religious learning in the 4.0 industrial revolution era?, and how is religious edu- cation in the 5.0 society era? are three problems in this research. This research uses a literature study approach. The data were analyzed by technical descriptive-analysis. The results of the analysis: The transformation of moral values, Hindu spirituality is absolutely needed as a tech- nological control for community education 5.0. Strengthening Hindu educational institutions, including: strengthening management, leadership, and policy reform by considering religious and moral values ??on the value of competence is an absolute requirement for the development of Hindu religious learning in the 5.0 era. It is hoped that the curriculum design with value requirements, delivery of material with the help of technology, is expected to be able to give birth to a whole Hindu generation, namely a generation that is fast-paced, precise, effective and efficient; a superior generation that is competitive, a generation that is creative, innovative, has character, is independent, loves the homeland and is religious in the era of society 5.0.